Plasma trans-Fatty Acid Concentrations Continue to Be Associated with Serum Lipid and Lipoprotein Concentrations among US Adults after Reductions in trans-Fatty Acid Intake. Issue 5 (5th April 2017) - Yang, Quanhe; Zhang, Zefeng; Loustalot, Fleetwood; Vesper, Hubert; Caudill, Samuel P; Ritchey, Matthew; Gillespie, Cathleen; Merritt, Robert; Hong, Yuling; Bowman, Barbara A
Abstract: Background: High intakes of trans -fatty acids (TFAs), especially industrially produced TFAs, can lead to unfavorable lipid and lipoprotein concentrations and an increased risk of cardiovascular disease. It is unknown how this relation might change in a population after significant reductions in TFA intake. Objective: This study, which used a new analytical method for measuring plasma TFA concentrations, clarified the association between plasma TFA and serum lipid and lipoprotein concentrations before and after the US FDA enacted TFA food-labeling regulations in 2006. Methods: Data were selected from the NHANES of 1999–2000 and 2009–2010. Findings on 1383 and 2155 adults, respectively, aged ≥20 y, were evaluated. Multivariable linear regressions were used to examine the associations between plasma TFA concentration and lipid and lipoprotein concentrations. The outcome measures were serum concentrations of total cholesterol (TC), LDL cholesterol, HDL cholesterol, and triglycerides and the ratio of TC to HDL cholesterol. Results: The median plasma TFA concentration decreased from 80.6 μmol/L in 1999–2000 to 37.0 μmol/L in 2009–2010. Plasma TFA concentration continued to be associated with serum lipid and lipoprotein concentrations after significant reductions in TFA intake in the population. For example, by comparing the lowest with the highest quintiles of TFA concentration in 1999–2000, adjusted mean (95% CI) LDL-cholesterol concentrations increased from 118 mg/dL (112, 123 mg/dL) to 135 mg/dL (130, 141 mg/dL) ( P -trend < 0.001). The corresponding values for 2009–2010 were 102 mg/dL (97.4, 107 mg/dL) and 129 mg/dL (125, 133 mg/dL) for LDL cholesterol ( P -trend < 0.001). Differences between the highest and lowest quintiles were consistent across age groups, sexes, races/ethnicities, and other covariates. Conclusions: Despite a 54% reduction in plasma TFA concentrations in US adults from 1999–2000 to 2009–2010, concentrations remained significantly associated with serum lipid and lipoprotein concentrations. There does not appear to be a threshold under which the association between plasma TFA concentration and lipid profiles might become undetectable.